Makna Leksikal Udang di Balik Batu dalam Ungkapan - Ayuni, Zelpi; Feranti, Nadila; Safitri, Meili; Hermandra, Hermandra (Prodi Perpustakaan dan Sains Informasi, 2023)
Language often changes along with the times and its speakers. Language as a means of expression and communication in human life such as in the fields of culture, science and technology. The development of the influence of the western world that makes changes to the language in Indonesia such as vocabulary and terminology. The research method used in this research is a type of qualitative research that is descriptive and carried out using analysis. The process and meaning are more cenerung in this study with theory as a foundation to focus on research in accordance with the field, the results and research of this study require in-depth analysis to obtain data. Lexical semantics refers to lexical meaning, or the meaning that exists in a lexeme even though there is no explicit context. For example, the lexeme buya (crocodile) has a lexical